First clinical applications for the NIR-II imaging with ICG in microsurgery - Wu, Yifan; Suo, Yongkuan; Wang, Zheng; Yu, Yifeng; Duan, Shuang; Liu, Hongguang; Qi, Baiwen; Jian, Chao; Hu, Xiang; Zhang, Dong; Yu, Aixi; Cheng, Zhen (Frontiers in Bioengineering and Biotechnology, 2022)
In microsurgery, it is always difficult to accurately identify the blood supply with ease, such as vascular anastomosis, digit replantation, skin avulsion reconstruction and flap transplantation. Near-infrared window I (NIR-I, 700—900 nm) imaging has many clinical applications, whereas near-infrared window II (NIR-II, 1,000–1700 nm) imaging has emerged as a highly promising novel optical imaging modality and used in a few clinical fields recently, especially its penetration distance and noninvasive characteristics coincide with the needs of microsurgery. Therefore, a portable NIR-II imaging instrument and the Food and Drug Administration (FDA) approved indocyanine green (ICG) were used to improve the operation efficiency in microsurgery of 39 patients in this study. The anastomotic vessels and the salvaged distal limbs were clearly visualized after intravenous injection of ICG. The technique enabled identification of perforator vessels and estimation of perforator areas prior to the flap obtention and made it easier to monitor the prognosis. Overall, this study highlights the use of the portable NIR- II imaging with ICG as an operative evaluation tool can enhance the safety and accuracy of microsurgery.